2005
DOI: 10.1161/circulationaha.104.529297
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxidized Low-Density Lipoprotein, a Strong Predictor for Acute Coronary Heart Disease Events in Apparently Healthy, Middle-Aged Men From the General Population

Abstract: Background-Oxidized LDL (oxLDL) is thought to play a key role in the inflammatory response in the arterial vessel wall. Methods and Results-In a prospective, nested, case-control study, the association between plasma oxLDL and risk of an acute coronary heart disease (CHD) event was investigated in men without prevalent CHD or diabetes mellitus at baseline. Subjects came from 2 population-based MONICA/KORA Augsburg surveys conducted in the years 1989 -1990 and 1994 -1995 with follow-up in 1998 (meanϮSD follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
148
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(169 citation statements)
references
References 59 publications
(37 reference statements)
12
148
1
8
Order By: Relevance
“…Coronary heart disease was also associated with a higher ox-LDL/LDLcholesterol ratio, which is consistent with previous studies [2][3][4]. Women with cancer also had a higher ox-LDL/LDL-cholesterol ratio than women without cancer in this study, which is consistent with a previous study that showed elevated ox-LDL in women with breast or ovarian cancer [30].…”
Section: Discussionsupporting
confidence: 92%
“…Coronary heart disease was also associated with a higher ox-LDL/LDLcholesterol ratio, which is consistent with previous studies [2][3][4]. Women with cancer also had a higher ox-LDL/LDL-cholesterol ratio than women without cancer in this study, which is consistent with a previous study that showed elevated ox-LDL in women with breast or ovarian cancer [30].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the oxidation of LDL-C by free radicals plays a central role in the formation, progression, and rupture of atherosclerotic plaques (27). A large body of evidence shows that ox-LDL is involved in the very early, yet critical steps of atherogenesis, such as endothelial injury, expression of adhesion molecules, and leukocyte recruitment and retention, as well as foam cell and thrombus formation (28). LDL-C is the main factor for the increase in ox-LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,24 Indeed, elevated oxLDL blood levels reflect the pathologic condition of the vessel wall, endothelial dysfunction and coronary plaque instability. 25 Furthermore, oxLDL increases endothelial stiffness, force generation and network formation. 20 There is also a report that SAA-LDL serves as a direct marker of arterial plaque activity in patients with stable coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%